Fatigue assessment of rib-deck welds in orthotropic steel decks integrating the effect of load dispersal through asphalt surfacing. (December 2020) - Wang, Qiudong; Ji, Bohai; Xia, Junyuan; Fu, Zhongqiu
Highlights: The mechanism of load dispersal through asphalt surfacing is clarified. Both discrete element model and finite element model are developed. Parametric analysis is conducted to investigate the characteristics of dispersed loads. Fatigue damage evaluation are performed integrating the load dispersal behaviour. Abstract: Fatigue evaluation of rib-deck welds combined with the effects of load dispersal through asphalt surfacing and temperatures is presented in this study. Firstly, both discrete and finite element models are developed to investigate the load dispersal through asphalt surfacing, as well as the factors affecting the load dispersal behaviour (LDB). Subsequently, parametric analysis was carried out to investigate the effects of temperature, pavement thickness and deck plate thickness on the LDB. Finally, the effect of LDB on fatigue performance of rib-to-deck welds is evaluated by taking into consideration the seasonal characteristics of ambient temperatures. Based on the investigations, the mechanism of LDB through asphalt surfacing is clarified, as well as the influencing mechanism of temperatures. Results show that the contact forces among aggregates, instead of bonding forces, mainly explain the load dispersal through asphalt surfacing. The effect of temperatures on the LDB is mainly related to the temperature sensitivity of the structural deformation. The dispersed wheel loads tend to concentrate above rib-to-deck welds rather than uniformly distribute onto the surface of OSDs. The effect of LDB on the fatigue performance of rib-to-deck weld is demonstrated to be negative at high temperatures; however, the overall effect in a year is positive due to the seasonal characteristics of ambient temperatures.